2018
DOI: 10.1039/c7tc04645f
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the synthesis method on the solid-state charge transport of radical polymers

Abstract: There are conflicting reports in the literature about the presence of room temperature conductivity in poly(2,2,6,6-tetramethylpiperidinyloxy methacrylate) (PTMA), a redox active polymer with radical groups pendent to an insulating backbone. To understand the variability in the findings across the literature and synthetic methods, we prepared PTMA using three living methods - anionic, ATRP and RAFT polymerization. We find that all three synthetic methods produce PTMA with radical yields of 70 - 80%, controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 45 publications
5
74
0
Order By: Relevance
“…Similarly with PVF‐CNT, PTMA‐CNT exhibited homogeneous and nanoporous morphology (Figure S2.3, Supporting Information), with a specific capacitance of 75.6 mAh g −1 estimated from galvanostatic measurements (Figure S1.6, Supporting Information). Electron paramagnetic resonance (EPR) measurements indicated a radical yield of 72.5% for the PTMA polymer (Figure S1.5, Supporting Information), which is in the comparable range to literature values …”
supporting
confidence: 83%
“…Similarly with PVF‐CNT, PTMA‐CNT exhibited homogeneous and nanoporous morphology (Figure S2.3, Supporting Information), with a specific capacitance of 75.6 mAh g −1 estimated from galvanostatic measurements (Figure S1.6, Supporting Information). Electron paramagnetic resonance (EPR) measurements indicated a radical yield of 72.5% for the PTMA polymer (Figure S1.5, Supporting Information), which is in the comparable range to literature values …”
supporting
confidence: 83%
“…2,[6][7] Zhang et al compared the conductivities of poly(2,2,6,6tetramethylpiperidinyloxy methacrylate) (PTMA) prepared by various synthetic routes and showed that varying the preparation conditions did not affect the radical yield or conductivities. 8 Recently, Joo et al reported an organic radical polymer exhibiting a remarkably high conductivity (20 S m -1 ) when prepared as a thin film, which is comparable to values reported for semiconducting conjugated polymers. 6 This enhanced conductivity was postulated to be the result of a self-organized percolating structure.…”
Section: Introductionmentioning
confidence: 69%
“…A high dispersity is undesirable because low‐molecular‐weight polymer chains dispersed within the electrode gradually dissolve into the electrolyte . In contrast, controlled‐radical polymerization usually yields PTMA with a low dispersity ( Ð <1.2), but it is exceedingly difficult to achieve high molecular weights (>24 000 g mol −1 ) because of reversible chain transfer . Single‐electron‐transfer living radical polymerization can yield even higher PTMA molecular weights of 169 000 g mol −1 , but capacity fade is still an issue.…”
Section: Introductionmentioning
confidence: 99%